Pneumothorax: An update on clinical spectrum, diagnosis and management - Beenish Iqbal; Rob Hallifax; Najib M. Rahman (Clinical Medicine)
Pneumothorax is defined as air in the pleural space and is characterised by chest pain and breathlessness. It is commonly divided into spontaneous and non-spontaneous subtypes based on the underlying mechanism. Chest X-ray is the most common investigation to diagnose and monitor pneumothorax, but CT-chest is being increasingly used to aid decision making in complex cases and to investigate an underlying lung disease. There should be a low threshold to investigate for an underlying familial or catamenial cause in suspected cases. Treatment for pneumothorax is based on clinical condition and symptoms of the patient rather than the size of pneumothorax. Conservative care can be offered to minimally symptomatic primary spontaneous pneumothorax patients, while needle aspiration, ambulatory Heimlich valve device and chest drain remain the interventional treatment options. Chest drain is a common treatment for patients with secondary spontaneous pneumothorax due to poor lung reserve. Recurrence after spontaneous pneumothorax is common and smoking cessation reduces the risk of future recurrence in active smokers. Surgical treatment with pleurodesis ± bullectomy should be considered for treatment of suitable patients with persistent air leak and for pneumothorax recurrence prevention in high-risk populations.